PENINGKATAN KINERJA KARYAWAN BERDASARKAN KERJASAMA TIM, KOMUNIKASI, DAN DISIPLIN KERJA (STUDI PADA KARYAWAN RESTAURANT KOREA MUJIGAE CABANG JABODETABEK BAGIAN OPERASIONAL) - Virnalisi, Silvi; Budhijana, Raden Bambang (Journal of Accounting, Management and Islamic Economics, 2025)
This research aims to examine improving employee performance based on teamwork, communication and work discipline. This research was canducted at the Mujigae Resto Jabodetabek branch in the Operations sections. Hypothesis testing in this research uses the PLS or Partial Least Square method with SmartPLS 4.0 software. The data collection technique uses a questionnaire distributed via Google form to collect respondent information. The sample in this study consisted of 34 employees of the Mujigae Resto Jabodetabek branch in the Operations department. The results of the analysis show that Teamwork, Communication and Work Discipline do not have a positive influence on Employee Performance.